IMPROVING THE ECONOMICREGULATIONOFWOMEN'S EMPLOYMENT - Nabikhajayeva Dilafroz Sobirdaughter (Uzbekistan Open Conference, 2025)
the article explores the employment problems of women living in working-age ruralareas. From the laws of the formation of employment with Labor, directions have been proposed toimprove the forms of ownership in the village, small and medium-sized entrepreneurship among ruralwomen, the development of workmanship again.
Keywords: localization; modernization; women’s employment; socio-economic mechanisms; women's entrepreneurship; small business; private entrepreneurship; family entrepreneurship; butchery